Prarancangan Pabrik Aluminium Fluorida dari Asam Fluosilikat dan Aluminium Hidroksida Kapasitas 40.000 Ton/Tahun - Handoyo, Virman, Eni Budiyati, S.T, M.Eng, Kun Harismah, Ph.D (2016)
AlF3 products needed by industry consolidation Al to lower the melting point of Al, so a great need for fuel for the heat of fusion can be reduced. AlF3 needs is increasing from year to year, particularly the developed countries that have a lot of industries Al in it such as China and India. This factory will be established in 2020 in Gresik with raw materials H2SiF6 and Al(OH)3 with production capacity of 40,000 tons/year. The reactor used is a reactor CSTR (Continuous Stirred Tank Reactor) which took place in the exothermic solid-liquid phase with the operating conditions of 70°C and a pressure of 1 atm. The next main process is crystallization and drying. To produce AlF3 with a capacity of 5050.505 kg / h takes H2SiF6 much as 8477.641 kg / hr and Al(OH)3 as much as 4518.540 kg/hour. While the need for water utilities as much as 2653.772 kg/hour of steam as much as 2666.488 kg/hour, as much as 1212.123 kW of electricity, compressed air as much as 115.582 kg/hour, the diesel fuel as much as 69.986 liters/hour and propane as much as 553.510 kg/hour. The factory operated for 330 days with the number of employees 202 people. The economic analysis shows the Percent Return on Investment (ROI) before tax of 35.5% and 26.6% after tax. Pay Out Time (POT) before taxes for 2.20 years and 2.73 years after tax for. Break Event Point (BEP) amounted to 49.38%, Shut Down Point (SDP) 27.97% and the Discounted Cash Flow (DCF) of 34.91%. Based on the above results and to consider several aspects such as operating conditions instrument with atmospheric pressure and low temperature, the raw material is not volatile and hygroscopic, waste does not damage the environment and location of the establishment of factories in the area of non-conflict, the plant AlF3 is profitable and feasible to set. Keyword: aluminium fluoride, aluminium hydroxide, fluosilicic acid